Pengklasifikasian Karya Sastra Berdasarkan DDC 23 - Rotmianto Mohamad (Universitas Wijaya Kusuma Surabaya, 2020)
Understanding about theories, rules, and instruction to classify literary works collections according to DDC 23rd Edition is important for a librarian. Because for many libraries, literary works probably are a dominant part of whole library materials so it’s must organize well according to DDC rules. As we are known, DDC has many rules and instructions to classify collection from all subjects. Then, this writing is to explain about the main rule to classify literary works collections according to DDC which it’s rule named “Origin of Literature” means literature is classed by the language in which originally written, with comprehensive explanation and some examples related so the right way to classify literary works collections will be easier to be understood. Keywords: classification, DDC 23, library collections, literary works.